Insulating Properties of Some Species of Wood - Kakkar, S. S. (Indian Forester, 1970)
The dielectric strength and dielectric constant of ten species of wood commonly grown in the jungles of Raipur Division, M.P. have been measured along and across the grain. The dielectric strength under instantaneous electric stress along the grain is found to vary from 5.8 K Volts/cm to 4.5 K Volts/Cm and across the grain from 19 to 13.7 K Volts/cm. Similarly the dielectric constant along the grain is found to vary from 3.35 to 2.83 and across the grain from 2.20 to 1.70.